DURATION OF DIABETES MELLITUS (DM) AND OBESITY IN PATIENTS WITH DIABETIC PERIPHERAL NEUROPATHY (DPN) TYPE II DIABETES MELLITUS - Anita Puji Rahayu; Muhareni Suryaningsih; Mila Sartika; Yulta Kadang (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Diabetic Peripheral Neuropathy (DPN) is a major complication in type II Diabetes Mellitus (DM) patients, with a steadily increasing prevalence. Data show that the incidence of DPN increased by 65% ​​in 80 patients undergoing treatment. The International Diabetes Federation (IDF) reported that in 2021, approximately 537 million adults worldwide suffered from DM. Obesity is known to increase the risk of developing DM by 2–3 times, while DM duration of ≥10 years plays a significant role in increasing chronic complications due to persistent insulin resistance. The high incidence of DPN prompted this study to analyze the association between duration of DM and obesity with DPN in type II DM patients. This study used a quantitative design with a correlational approach. Data were collected through observations of 80 type II DM patients who underwent examinations during the study period. Analysis was performed using the Spearman Rank correlation test to assess the strength and direction of the association between duration of DM, obesity based on Body Mass Index (BMI), and DPN incidence. The analysis results showed a significant positive correlation between the duration of DM and the incidence of DPN (r = 0.324; p = 0.003), indicating that the longer a person suffers from DM, the higher the risk of developing peripheral neuropathy. Conversely, no significant association was found between the duration of DM and obesity (r = -0.180; p = 0.110), nor between obesity and the incidence of DPN (r = 0.060; p = 0.598). These results highlight the importance of long-term DM management to prevent complications of Diabetic Peripheral Neuropathy (DPN)